The Effect Of Using The Discovery Learning Method On Students' Science Learning Outcomes In Grade IV - Desy Crismas Silaban; Eduardo Sianturi; Maria Kendari Siregar; Derinta L.R. Padang (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
The learning method chosen by the teacher has an important role in the teaching and learning process, so that students will feel interested and motivated to actively participate in finding solutions to problems, not just receiving information, so that conducive learning objectives can be achieved. However, many students still have low learning outcomes, so that learning objectives are not achieved. This is also caused by a lack of understanding and motivation of students. This study aims to determine the effect of the discovery learning method on science learning outcomes of students in grade IV of SDN 091528 Siligason. This study was located at SDN 091528 Siligason with research respondents of grade IV students totaling 25 students. This study is a quantitative type with an experimental method. The data in this study were tested for analysis requirements with a normality test with the Lilifors test and a homogeneity test with the F test. Then the hypothesis was tested with a t test. Based on the results of the study, it is known that the average value of science learning outcomes of grade IV students of SDN 091528 Siligason with the application of the discovery learning method obtained a standard score of 75.62. The average value of the science learning outcomes of grade IV students of SDN 091528 Siligason without the application of the discovery learning method obtained a value of 67. With the calculated t (1,99) being greater than the t table (1,66), there is an influence of the application of the discovery learning method on the science learning outcomes of grade IV students of SDN 091528 Siligason